2019
DOI: 10.1007/jhep10(2019)260
|View full text |Cite
|
Sign up to set email alerts
|

The scales of black holes with nAdS2 geometry

Abstract: We study nearly extreme black holes with nearly AdS 2 horizon geometry in various settings inspired by string theory. Our focus is on the scales of the nAdS 2 region and their relation to microscopic theory. These scales are determined by a generalization of the attractor mechanism for extremal black holes and realized geometrically as the normal derivatives along the extremal attractor flow. In some cases the scales are equivalently determined by the charge dependence of the extremal attractor by itself. Our … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
(73 reference statements)
0
21
0
Order By: Relevance
“…The connection between JT gravity and near-extremal black holes has been widely discussed in past literature [38][39][40][41][42][43][44][45][46][47][48][49][50]. In fact, in [38], the scale M gap defined through the thermodynamics was identified as the symmetry breaking scale for the emergent nearhorizon AdS 2 isometries, SL(2, R).…”
Section: Jhep05(2021)145mentioning
confidence: 99%
“…The connection between JT gravity and near-extremal black holes has been widely discussed in past literature [38][39][40][41][42][43][44][45][46][47][48][49][50]. In fact, in [38], the scale M gap defined through the thermodynamics was identified as the symmetry breaking scale for the emergent nearhorizon AdS 2 isometries, SL(2, R).…”
Section: Jhep05(2021)145mentioning
confidence: 99%
“…And so the persistent trend in nAdS 2 holography, coined with a 'n' since we are 'near' to our original configuration, is that the deviations away from extremality are controlled by this pattern. For a review see [14].The application of this new framework to black hole physics has shown that, while JT models capture common features [15][16][17][18][19][20], the additional parameters for more general black holes display interactions that are not present in JT gravity [21][22][23][24][25][26][27]. This makes clear that there is new phenomena to be explored, that simpler models do not take into account.Our interest therefore is to further explore the properties of nAdS 2 /nCFT 1 with the goal of building a more refined understanding of the dynamics near the horizon of (near-)extremal black holes.…”
mentioning
confidence: 99%
“…In order to establish this we adapt the nearAdS attractor mechanism known in higher dimensions [45,46] to BTZ black holes [47,48]. Accordingly, consider a general asymptotically AdS 3 geometry of the form…”
Section: Jhep07(2021)038mentioning
confidence: 99%